(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
Fern species under family Thelypteridaceae and Nephrolepidaceae tend to have similarities when it comes to leaf morphology. Due to their cohesive morphological appearance, species under these two families are hard to distinguish from the other. While qualitative descriptions in leaf shape could aid in understanding the identification, evolution and development of ferns, it is argued that the quantitative description of the shape of the pinna is a good measure in the classification of ferns by delineating species. This study was therefore conducted to quantitatively describe the pinna shape of five species of ferns under family Thelypteridaceae and four species under family Nephrolepidaeceae by Elliptic Fourier Analysis (EFA). Significant shape variations were observed within and between species specifically in width, apex and base of the pinna. Species found on shaded habitat were observed to have broader pinna lamina compared to elongated and narrow pinna of fern species found on open areas. Light availability is argued to possibly influenced the pinna shapes of the ferns. Results of this study have shown the importance of EFA in the quantitative description of biological shape that aid in understanding the relationships of the fern species.